Pashechko M., Berezhanskyi T. Raising the wear resistance for working elements fire equipment by applying coatings based on eutectic Si, Ni, Cr – doped alloys of Fe-Mn-C-B. - Пашечко, М.І.; Бережанський, Т.Г. (Problems of Tribology, 2016)
In modern society in extinguishing fires and emergencies of natural and man-made disasters, fire and rescue de-partments have to work in extremely difficult and dangerous conditions. Thus the quality and reliability of fire equipment and rescue equipment used by rescuers may depend not only the life of the victims, but also their own. Today in emergency de-partments often use techniques and equipment which are partly worn out and have lifetime or service life. Discovered eutec-tic material in the study marked the lowest mass loss at high loads, we can state that the material can be used for the applica-tion of the working elements of fire equipment and rescue equipment that operate at high loads in order to increase their du-rability, and result resource increase their performance and service life. Keywords: Fire appliances, eutectic coating, friction, burden, wear resistance.